Atmospheric cold plasma treatment of soybean protein isolate: insights into the structural, physicochemical, and allergenic characteristics. Issue 1 (17th December 2020) - Zhang, Qiaozhi; Cheng, Zhouzhou; Zhang, Jianhao; Nasiru, Mustapha Muhammad; Wang, Yanbo; Fu, Linglin
Abstract : Abstract: Currently, there has been a surge of interest in revealing the interactions between plasma and food matrices. In this study, we investigated the impacts of atmospheric cold plasma (ACP) treatment on the structural, physicochemical and allergenic characteristics of soybean protein isolate (SPI). SPI dispersions were subjected to ACP treatments at different frequencies (80 to 100 Hz) and durations (1 to 10 min) to investigate the effects of exposing conditions. Results showed that ACP induced reactive oxygen species‐mediated oxidation of soy proteins, resulting in modifications in the secondary and ternary structures of SPI. As a consequence, functional properties of SPI, such as emulsifying (56 to 168%, compared with control) and foaming properties (60 to 194%) were influenced by varying degrees. In addition, under certain circumstance (120 Hz, 5 min), the IgE‐binding level of SPI was decreased by up to 75%, when compared to the control. Moderate treatment yielded products with improved functionality and reduced allergenicity, while extensive exposure induced a loss of vendibility due to protein aggregation. Practical Application: In this study, we demonstrated for the first time, that plasma species reacted with soybean proteins, resulting in spatial structural changes which are closely related with protein functionality and allergenicity. ACP interacts with macromolecules in aqueous systems and thus can be an alternative and promising nonthermal approach in modifying soybean proteins, whereas the exact role of different processing parameters needs to be well‐elaborated.